Identification of Peridotite Bedrock using Resistivity Geoelectric Method in Lapao Pao Estuary Area, Kolaka District - Haraty, Syamsul Razak; Gusan, Muhammad; Hasan, Erzam Salahuddin (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
Ultramafic rocks are the main source of nickel laterite deposits. One of the areas that has an ultramafic complex is located in Muara Lapao Pao Village, Kolaka Regency. The research was conducted in the mining area of PT Tri mitra Babarina Putra using the resistivity geoelectric method of the Wenner - Schlumberger configuration, In the area it is not yet known exactly how much peridotite bedrock is present in the subsurface. Therefore, it is necessary to conduct a geophysical survey in identifying the occurrence of peridotite bedrock, and can determine the depth and thickness of peridotite bedrock in the research area. the occurrence of peridotite bedrock in the mining area of PT Tri Mitra Babarina Putra has a resistivity value between 3000 – 17984 Ohm-meters. Peridotite bedrock in the research area on all four tracks has a depth and thickness that is almost uniform. lines 1 and 2 and 4 are at a depth of 34.5 - 39.6 meters with a thickness of up to 5.1 meters. and line 3 peridotite bedrock is at a depth of 40 m to more. There are 3 layers in the study area, namely, soil/overburden layer with a resistivity value of 16.5 – 122 Ohm-meters, serpentinite rock layer with a resistivity value of 200 – 2438 Ohm-meters and peridotite bedrock layer with a resistivity value of 3000 – 17984 Ohm-meters.